Revolutionizing Justice: The Game-Changing Role of E-Litigation in Civil Case Evidence in Indonesia - Auliya Rochman; Filiyah Chandra Asrini; Ari Kusuma Wibowo; Nucharee Nuchkoom Smith (Jurnal Hukum Replik, 2025)
ThisÂ paper examines the transformative impact of e-litigation on civil case evidence in Indonesia, particularly in light of the rapid advancement of science and technology. In response to contemporary legal challenges, the Indonesian Supreme Court introduced the Electronic Litigation (e-Litigation) system, initially outlined in Supreme Court Regulation Number 3 of 2018 and subsequently refined in Regulation Number 1 of 2019 and Regulation Number 7 of 2022. These regulations aim to modernize case administration and enhance the efficiency of judicial processes. This study utilizes a qualitative approach, incorporating juridical-empirical research through interviews and literature reviews to assess the effectiveness of e-Litigation at the Semarang District Court. Findings indicate that while e-Litigation has the potential to streamline evidence presentation and case resolution, its implementation has not been fully optimized due to regulatory complexities. Challenges in the systematic handling of electronic evidence impede the realization of justice that is simple, fast, and cost-effective. The research highlights the necessity for ongoing training and support activities to improve the use of electronic evidence in civil cases. Ultimately, this study underscores the significance of embracing e-litigation not only to modernize the Indonesian legal framework but also to foster greater public trust in the judicial system, paving the way for a more equitable legal environment.